Surgical Causes of Significant Intraoperative Neuromonitoring Signal Changes in Three-Column Spinal Surgery - Wi, Seung Myung; Park, Sang-Min; Chang, Sam Yeol; Lee, Jeongik; Kim, Sung-Min; Chang, Bong-Soon; Kim, Hyoungmin (Asian spine journal, 2021)
Study Design: Retrospective case series.Purpose: To evaluate the risks and causes of neurologic complications in three-column spinal surgery by analyzing intraoperative neurophysiological monitoring (IONM) data. Overview of Literature: Three-column spinal surgery, which may be required to correct complex spinal deformities or resection of spinal tumors, is known to carry a high risk of neurologic complications. However, few studies reported a specific surgical procedure related to a significant IONM signal change during surgery.Methods: Multimodality IONM data, including somatosensory-evoked potentials (SSEP) and motor-evoked potentials (MEP), were reviewed in 64 patients who underwent three-column spinal surgery from 2011 to 2015. Surgical procedures included posterior vertebral column resection, pedicle subtraction osteotomy, total en bloc spondylectomy, piecemeal spondylectomy, and corpectomy with laminectomy (n=27) in three cervical, 34 thoracic, and 31 lumbar procedures.Results: Significant IONM signal changes occurred in 11 of 64 (17.1%) patients. SSEP and MEP were changed in 11 patients. Postoperative neurologic deterioration occurred in 54.5% (6 of 11) of the patients, and two of them were permanent. There was no postoperative neurologic deterioration in patients without significant signal change. Suspected causes of IONM data changes are as follows: adhesion/tethering, translation, contusion, and perfusion.Conclusions: Based on the results of this study, to enhance neurologic safety in three-column spinal surgery, surgeons should pay attention to protect the spinal cord from mechanical insult, especially when the spinal column was totally destabilized during surgery, and not to compromise perfusion to the spinal cord in close cooperation with a neurologist and anesthesiologist.